S46 Outcome after pulmonary endarterectomy (PEA): Long term follow-up of the UK national cohort. (14th November 2013) - Cannon, J; Page, K; Roots, M; Ponnaberanam, A; Tracy, C; Taboada Buasso, D; Sheares, K; Ng, C; Dunning, J; Tsui, S; Pepke-Zaba, J; Jenkins, D
Abstract : Introduction: Chronic thromboembolic pulmonary hypertension (CTEPH) is a life threatening condition that historically has a poor outcome with supportive medical treatment. Pulmonary endarterectomy (PEA) is the treatment of choice and offers the only chance of cure. Data on the long term survival after PEA are limited. Method: All patients who have undergone a PEA for CTEPH at Papworth hospital were included between January 1997 and November 2012. Patients who had a re-do operation were excluded. Pre- and post-operative data on haemodynamics, exercise capacity, functional class and targeted PAH therapies taken were obtained from our PH database and from other UK PH centres. The long-term survival of patients who returned for follow-up at 3 months post PEA was determined using the NHS spine summary care record tracking system. Overseas patients were censored when last seen. Results: 880 patients underwent PEA over the 15 year period. The mean age was 57 (range 15–84) and 53% were male. The majority (89%) were in WHO functional class 3 or 4 prior to surgery with an average mean pulmonary artery pressure (mPAP) of 47 mmHg and PVR of 795 dynes. 65% of patients were taking at least 1 targeted therapy as a "bridge to surgery". Post surgery the majority of patients (86%) were in WHO functional class 1 or 2 at the 12 month follow-up with only 17% taking targeted therapy. There was a reduction in the average mPAP to 27 mmHg and PVR to 308 dynes by 12 months. The 10 year conditional survival post PEA of the first 314 patients from the cohort (Freed et al . J Thorac Cardiovasc Surg, 2011;141:383–7) was 74%. Conclusion: The conditional survival of a subset of the cohort at 10 years was 74%. There was a significant functional and haemodynamic improvement in the majority of patients at 12 months post surgery. Only 17% of patients at 12 months post surgery were being treated with targeted therapy. Acknowledgements: The authors would like to acknowledge the pulmonary hypertension centres in the UK. " This research was supported by the National Institute for Health Research (NIHR) Cambridge Biomedical Research Centre ".